A preliminary economic analysis of the process of decarbonising an oil-exporting country: the case of Libya - Rawesat, Abdulwahab; Pilidis, Pericles (MDPI, 2024)
This paper offers a basic analysis for strategic decision-makers of the process when an economy shifts from oil to non-carbon energy exports and zero carbon emissions. The fundamental concept is how to offer environmental performance without causing an economic contraction. The costs and feasibility of solar, wind, and helium closed-cycle technologies are thoroughly and independently compared. Solar panels make up 0.67% of the USD 1.14 trillion total cost of solar energy, which is the capital investment, with panels accounting for 0.51%. Future technical developments are expected to bring down the cost of such solar farms to USD 0.74 trillion. Turbines comprise 66% of the estimated USD 0.67 trillion wind energy costs. At USD 0.36 trillion, helium closed-cycle gas turbines—which account for 0.78% of the overall cost—are essential for stabilising energy output. With a focus on cost viability, this analysis offers direction for Libya’s transition to energy self-sufficiency and export, in support of global carbon reduction targets. It also offers unique insights into areas not previously covered by other studies. This paper’s unique contribution is its economic analysis of the decarbonisation of an entire oil-exporting nation.
Keywords: 38 Economics; 4104 Environmental Management; 41 Environmental Sciences; 7 Affordable and Clean Energy; decarbonisation strategies; wind turbine; hydrogen combined-cycle gas turbine; hydrogen production; national data analysis; energy consumption; green economy; energy self-sufficiency